Design and analysis of hybrid firefly algorithm-pattern search based fuzzy PID controller for LFC of multi area power systems - Sahu, Rabindra Kumar; Panda, Sidhartha; Pradhan, Pratap Chandra (International journal of electrical power & energy systems, 2015)
•A hybrid FA and PS optimized fuzzy PID controller is proposed for LFC of multi-area power system.•Proposed approach exhibits better performance than DE and CPSO approaches.•Sensitivity analysis is performed to show the robustness of the proposed controllers.•The study is extended to a three unequal area by considering the physical constraints.•Parameters of the proposed controllers need not be reset with system parameter variation. A hybrid Firefly Algorithm (FA) and Pattern Search (PS) optimized fuzzy PID controller is proposed for Load Frequency Control (LFC) of multi area power systems. Initially a two area thermal system with Governor Dead Band (GDB) nonlinearity is considered and the gains of the fuzzy PID controller are optimized employing a hybrid FA and PS (hFA–PS) optimization technique. The supremacy of proposed hFA–PS over FA is also demonstrated. The advantage of the proposed fuzzy PID controller has been shown by comparing the results with some recently published techniques, such as Differential Evolution (DE) and Craziness based Particle Swarm Optimization (CPSO). Further, sensitivity analysis is performed by varying the system parameters and operating load conditions from their nominal values. It is observed that the optimum gains of the proposed controller need not be reset even if the system is subjected to wide variation in loading condition and system parameters. Additionally, the proposed approach is further extended to three unequal area thermal systems with physical constraints such as time delay, reheat turbine, Generation Rate Constraint (GRC) and GDB nonlinearity. It is observed that the proposed technique is able to handle nonlinearity and physical constraints in the system model.